FRI0389 TOWARDS ONE-STAGE ARTICULAR CARTILAGE REPAIR USING DEVICE BASED ARTHROSCOPIC MECHANICAL RELEASE OF SYNOVIAL MESENCHYMAL STEM CELLS WITH CHONDROGENESIS AUGMENTATION WITH AUTOLOGOUS PLATELET CONCENTRATE WITHOUT CELL CULTURE EXPANSION. (2nd June 2020) - Altaie, A.; Jones, E.; Wall, O.; Mcgonagle, D.
Abstract : Background: Synovial fluid contains resident mesenchymal stem cells (SF-MSCs) that are derived from the synovial membrane and may interact with superficial cartilage injury sites. We previously reported on a novel methodology for increasing the number of MSCs in the knee joints using synovial brushing combined with platelet lysate (PL) as a chondrogenic inducer [1, 2]. Objectives: The purpose of this study was to evaluate autologous and allogenic PL as a chondrogenic inducer and the chondrogenic potential of the mobilised MSCs without further ex vivo expansion. The desired goal of the study was to provide in vitro proof of concept of direct chondrogensis without resort to MSC expansion protocols, since adequate MSCs towards repair could be mechanically procured in a minimally invasive fashion. Methods: SF-MSCs were derived from the joint cavity of patients undergoing arthroscopy procedures. For the mechanical release of MSCs 'before' and 'after' brushing the synovium with the novel device (Figure 1A ), samples of irrigation fluid were collected and MSC numbers were evaluated by CFU-F assay and flow cytometry for stromal and immune populations. Standard chondrogenic assay was performed on uncultured and cultured expanded synovial MSCs. Pellet cultures were maintained in complete chondrogenic media (CCM), DMEM+50% autologous filtared platelet concentrate (fPC), 50% Stemulate (allogeneic human PL; Cook Regentec, Indianapolis, IN), or expansion media (control). Chondrogenesis was assessed by Glycosaminoglycan (GAG) and Toluidine blue staining. Autologous blood was processed through a gravity-based filtration system, HemaTrate ® (HT; Cook Regentec, Indianapolis, IN), to produce a PC. Results: Mechanically mobilized SF-MSC numbers increased as measured by CFU-F assay and flow cytometry for CD90 High CD45 Low cells (p<0.001), and CD14 + HLA-DR + CD206 + CD86 + M2 macrophages also increased (p<0.05). The HT system significantly concentrated platelets and WBCs by 6- (p<0.0001) and 1.8-folds (p<0.001), respectively. Device-mobilized SF-MSC proliferation significantly increased after 6 days in DMEM + 10% PC (p<0.001) and correlated with PC platelet number (p<0.005). Autologous PC increased GAG levels compared to control (p<0.0001), and there was no significant difference compared to allogenic PL (p>0.5). Uncultured synovial cells produced significantly more GAG when cultured in CCM or DMEM + 50% autologous PC compared to control (p<0.0001). The GAG levels of uncultured synovial cells positively correlated with CFU-F (p<0.005). Chondrogenic potential of uncultured synovial cells that were mechanically mobilized with initial irrigation exhibited an increase (1.5-fold) in GAG levels (p<0.001) figure 1 -B and also positively correlated with CFU-F (p<0.005). Conclusion: Synovial MSCs can be mechanically released in sufficient number to undergo in vitro chondrogenic induction with significant chondrogenic activity without the need for ex vivo culture expansion. In vitro, autologous PC can be used as chondrogenic inducer for uncultured SF-MSCs. The data presented here supports one stage arthroscopy procedures for cartilage repair References: [1]T.G. Baboolal, S.C. Mastbergen, E. Jones, S.J. Calder, F.P. Lafeber, D. McGonagle, Synovial fluid hyaluronan mediates MSC attachment to cartilage, a potential novel mechanism contributing to cartilage repair in osteoarthritis using knee joint distraction, Annals of the rheumatic diseases 75(5) (2016) 908-15. [2]A. Altaie, T.G. Baboolal, O. Wall, E. Jones, D. McGonagle, Platelet lysate enhances synovial fluid multipotential stromal cells functions: Implications for therapeutic use, Cytotherapy 20(3) (2018) 375-384. Disclosure of Interests: Ala Altaie: None declared, Elena Jones: None declared, Owen Wall: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC